Survival of patients receiving systematic therapy for metachronous or synchronous metastatic renal cell carcinoma: a retrospective analysis - Sung Han Kim (BMC Cancer, 2019)
Abstract Background The differences in progression-free survival (PFS) and cancer-specific survival (CSS) of metastatic renal cell carcinoma (mRCC) patients according to treatment, type of metastasis, and Heng criteria risk are unclear. In this study, we compared survival according to various such parameters. Methods Between 2000 to 2014, 214 mRCC patients, of whom 171 (79.9%) were intermediate-risk and 43 (20.1%) were poor-risk, were retrospectively selected; 126 (58.9%) patients were treated with immunotherapy (IT) and 88 (41.1%) with targeted therapy (TT). Moreover, 144 patients had synchronous mRCCs (67.3%, SM) and 70 had metachronous mRCCs (32.7%, MM). The Kaplan-Meier method and log-rank test were used to compare progression-free survival (PFS) and CSS. Results During a median 4.2 (1.0–70.4) months of systemic treatment and 98.3 (4.8–147.6) months of follow-up, the median PFS and CSS were 4.7 (95% confidence interval [CI]: 3.8–5.5) and 13.8 (95% CI, 9.8–18.3) months, respectively. The PFS and CSS were significantly better in the MM (5.9 and 21.3 months) and intermediate-risk groups (5.2 and 18.3 months) than those in the SM (4.4 and 9.6 months) and poor-risk groups (2.7 and 5.8 months), respectively (p < 0.05). Further stratification showed that TT produced significantly better PFS than IT in intermediate-risk patients with SM and a treatment-free interval (TFI) < 1 year, and in those with MM with a TFI ≥1 year (p < 0.05). There were no differences in survival outcomes according to various other subgroup stratifications (p > 0.05). Conclusion Dividing patients into specific subcategories helps to better predict therapeutic outcomes.